Catherine, called Birdy - Cushman, Karen (New York, NY Harper Trophy, 1994)
The thirteen-year-old daughter of an English country knight keeps a journal in which she records the events of her life, particularly her longing for adventures beyond the usual role of women and her efforts to avoid being married off.
Keywords: Middle Ages -- Fiction; Diaries -- Fiction; England -- Fiction